INTERNAL CONTROL AND RISK MANAGEMENT ON FRAUD PREVENTION IN FINANCIAL STATEMENTS - Awaluddin Awaluddin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Why is fraud high in financial statements? This is because bias towards the organization leads to serious risks and losses to the organizations and other stakeholders. Therefore it becomes necessary to find ways in which such issues may be avoided in the first place. The research method that has been employed is the literature research method. The research findings confirmed that both internal control and risk management positively affect the level of fraud occurrence in financial statements. Although, the emphasis of this study was on the need for strong internal control and proper deployment of risk management as an aspect of fraud risk management in financial statements.